2020
DOI: 10.23887/jjpe.v12i1.24294
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Keaktifan Mahasiswa dalam Proses Pembelajaran Statistika Mulitvariat

Abstract: This research is motivated by the condition of students in the learning process of multivariate statistics courses. In the matter of data input practice, data output, and data interpretation. Students tend to only follow lectures and are less active in asking questions. Students are less active in looking for additional material beyond the material taught by the lecturer. The research method uses a qualitative case study type approach. The research object consisted of 23 students who took multivariate courses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
1
6
0
5
Order By: Relevance
“…Referring to the data presentation of the research results, it is known that in the one-to-one test class (department of physics education), the average activity of the lecturers is included in the very practical category. The findings in this study are relevant to (Irsyad, 2020), who have received the findings of the lecturer carrying out learning guided by the plans that have been prepared. In this study, the lecturer's activities refer to the planning document as a control for the implementation of the learning syntax (Sitepu & Lestari, 2018;.…”
Section: Figure 1 Implementation Of Learning By Lecturers On the One ...mentioning
confidence: 94%
“…Referring to the data presentation of the research results, it is known that in the one-to-one test class (department of physics education), the average activity of the lecturers is included in the very practical category. The findings in this study are relevant to (Irsyad, 2020), who have received the findings of the lecturer carrying out learning guided by the plans that have been prepared. In this study, the lecturer's activities refer to the planning document as a control for the implementation of the learning syntax (Sitepu & Lestari, 2018;.…”
Section: Figure 1 Implementation Of Learning By Lecturers On the One ...mentioning
confidence: 94%
“…Keaktifan siswa selama proses kegiatan belajar mengajar adalah salah satu indikator adanya rasa ingin tahu. Salah satu indikator keberhasilan proses pembelajaran adalah ketika keterlibatan siswa aktif didalamnya (Irsyad, Wuryandini, Yunus, & Hadi, 2020). Keaktifan siswa saat proses pembelajaran akan menyebabkan interaksi yang tinggiantara siswa dengan gurunya sehingga akan terjadi komunikasi yang efektif.…”
Section: Hasil Dan Pembahasanunclassified
“…The success of a learning process is influenced by many things, including by lecturers and students themselves. According to Sani, [7] if students and lecturers contribute actively in a learning process, then the learning will run. effectively.…”
Section: Introductionmentioning
confidence: 99%
“…From some of the descriptions above, it can be concluded that active interaction in a learning process is very important, because: (1) Learning will not be carried out properly without interaction between learning components (teachers, students, objectives, materials, media, methods, and evaluation), by interacting students have the courage to communicate in their environment, students are brave and able to explain things, and are able to negotiate. (2) Lack of interaction can slow down the formation of assessment and reasoning in lessons, (3) If there is no interaction, there will be a tendency for interaction to be dominated only by lecturers during lectures, (4) Student interaction activity needs to be increased to achieve learning objectives, (5) When students are active in the learning process, the percentage of learning success will increase, (6) The lecturers also get feedback, namely knowing whether the material that has been delivered can be accepted and understood by students well, and lastly (7) Interaction in The world of education, especially for educators and students, is very important so that the dynamics of education run well.…”
Section: Introductionmentioning
confidence: 99%